2015
DOI: 10.1007/s11481-015-9620-2
|View full text |Cite
|
Sign up to set email alerts
|

An Act of Balance Between Adaptive and Maladaptive Immunity in Depression: a Role for T Lymphocytes

Abstract: Historically the monoaminergic neurotransmitter system, in particular the serotonergic system, was seen as being responsible for the pathophysiology of major depressive disorder (MDD). With the advent of psychoneuroimmunology an important role of the immune system in the interface between the central nervous systems (CNS) and peripheral organ systems has emerged. In addition to the well-characterised neurobiological activities of cytokines, T cell function in the context of depression has been neglected so far… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
47
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(53 citation statements)
references
References 135 publications
1
47
0
2
Order By: Relevance
“…A similar impairment of the adaptive immune response has been reported in depression, in particular, decreases in NKC cytotoxicity and reduced mitogen-stimulated T-lymphocyte proliferation (Blume et al, 2011; Irwin and Miller, 2007; Miller, 2010; Toben and Baune, 2015; Zorrilla et al, 2001). Consistent with these data, depressed individuals show a decreased response to viral vaccines (Irwin et al, 1998; Irwin et al, 2013), and reportedly, a worse prognosis in cases of infectious disease (Leserman, 2008) and cancer (Sephton et al, 2009).…”
Section: Introductionsupporting
confidence: 72%
See 1 more Smart Citation
“…A similar impairment of the adaptive immune response has been reported in depression, in particular, decreases in NKC cytotoxicity and reduced mitogen-stimulated T-lymphocyte proliferation (Blume et al, 2011; Irwin and Miller, 2007; Miller, 2010; Toben and Baune, 2015; Zorrilla et al, 2001). Consistent with these data, depressed individuals show a decreased response to viral vaccines (Irwin et al, 1998; Irwin et al, 2013), and reportedly, a worse prognosis in cases of infectious disease (Leserman, 2008) and cancer (Sephton et al, 2009).…”
Section: Introductionsupporting
confidence: 72%
“…This perspective evolved from the stress literature which demonstrated that chronic psychological stressors were associated with declines in the total numbers of circulating B-cells and T-cells, reduced mitogen-induced lymphocyte proliferation and natural killer cell (NKC) activity, and the mobilization of regulatory T-cells (T reg ), along with greater susceptibility to viral infections, reduced immune responses to vaccines, reactivation of latent herpesviruses, and slowed wound healing (Dhabhar, 2014; Glaser and Kiecolt-Glaser, 2005; Irwin, 2008; Toben and Baune, 2015). This impairment in the adaptive immune response is hypothesized to be mediated by the suppressive effects of cortisol on the expression of anti-viral genes as well as the effects of adrenergic signaling on the expression of type I interferons (Irwin and Cole, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Lately, some excellent reviews on the role of T cells in mood disorders have been published (7) (8) (9). T cells are essential for antigen-specific cell-mediated immune responses.…”
Section: Introductionmentioning
confidence: 99%
“…The present idea is that in patients with an active mood disorder a pro-inflammatory state prevails with raised numbers of T h 17 cells and reduced numbers of T regs , while in mood disorder patients in remission/recovery normal number of T cells can be found. Yet T cells seems to have an impaired capability for expansion and an increased apoptosis when stimulated with a mitogen (9).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to neurotrophic factors, important roles for inflammatory mediators are evident in pathophysiology of a variety of neuropsychiatric disorders including MDD (Felger and Lotrich 2013; Postal and Appenzeller 2015; Toben and Baune 2015). This is supported by the results of numerous studies indicating elevated levels of the pro-inflammatory cytokines such as tumor necrosis factor (TNF)-α and interleukin (IL)-1β in plasma of depressed patients (Gold and Irwin 2009; Felger and Lotrich 2013; Toben and Baune 2015).…”
Section: Role Of Inflammatory Mediatorsmentioning
confidence: 99%